QUALITY OF FRESH STRAWBERRY (Fragaria sp cv. HOLIBERT ) FROM KETEP MAGELANG CENTRAL JAVA AND ITS STORAGE IN TROPICAL ENVIRONMENT - Mohammad Affan Fajar Falah; Putri Yuliastuti; Risma Hanifah; Pujo Saroyo; Jumeri Jumeri (BPFP Faperta UNIB, 2018)
Strawberry (Fragaria sp cv Holibert) is a non-climakteric fruit which have high value with high consumer demand. Tropical environment conditions can deteriorate and decrease quality of their fruit. Objective of the research were to identify quality characteristics of fresh strawberry that storages in tropical environment with and without temperature controlled.Strawberry fruit were sampled from mountain area in Ketep, Magelang, Central Java. Several quality parameter were measured include physical parameter (fresh weight, weight loss, skin texture and color) and chemical parameter (water content, soluble solid content, vitamin C and titratable acidity). Then, fresh weight of strawberry were compared with IQS 8026-2014 using control chart. Storage conditions were tropical condition without controlled temperature and controlled temperature at 4 oC and 10 oC. Result shown that chemical parameters of fresh strawberry were optimum at 4 oC storage condition for water content and soluble solid content. Physical parameter of fresh starwberry were better conditions at controlled environment. The standard quality was confirmed with class 1 for weight averages >15-20 g/fruit for best fruit . Tropical conditions were deteriorate quality and shortage shelf life of the strawberry.